Pembuatan Sistem Informasi Geografis Untuk Pemetaan Sebaran Lokasi Distribusi Pemasaran Produk Batu Marmer Politeknik Aceh Selatan - Safridatul Audah; Bakruddin Bakruddin (Jurnal Inotera, 2017)
South Aceh Regency has abundant mine products, one of which is marble. Polytechnic of South Aceh Particularly UPT Marmer Industrial Engineering Study Program performs processing of marble in the form of marble processed into the form of crafts, such as tables, chairs, glasses, ashtrays, and so on, and spread in various areas that have been distributed, but the marketing of marble production not all is known by the community, so it is necessary to find a solution to be able to mapping the location of marble marketing in order to increase production output to be distributed to the consumer of various regions. This research is expected to produce Geographic Information System for mapping of marketing location of marble production of Polytechnic of South Aceh so that society can know marble marketing center in Aceh region.